COMPONENTS OF TECHNOLOGIES FOR FORMING INTEGRATED THEORETICAL KNOWLEDGE IN FLIGHT SCHOOLS - Смирнова, І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The subject of this article is the technology of integrative theoretical knowledge formation with cadets-pilots while studying special courses at higher flight educational institution. The author gave a definition of "integrative theoretical knowledge of cadets - pilots". The process of forming integrative professional knowledge, skills and abilities of special subjects is recommended to be based on the use of intersubject communications. The author reveals the best ways of expanding and deepening the intersubject communications when structuring training methodology for training cadets-pilots in special courses at higher flight educational institutions. The technology of applying intersubject communications as a didactic problem has a multi-vector nature, since it covers the content, methods and forms of training at higher flight school. To create training technology the author bases himself on the methodological items of the system concept that regard creation of future pilots integrative knowledge to be a multi component structure the goal of which is the system creating factor. As soon as the goal is achieved by solving numerous problems to get the common set result the author based on inter subject communications to specify problems for theoretical training of cadets-pilots in special subjects. The content of special courses training technology for cadets should ensure high level of reliability based on knowledge, skills and abilities. Methods of training are structure components of integrated theoretical knowledge formation technology. The variety of organizational forms is an important condition for the effective training of future pilots. In accordance with the accepted forms and selected methods of future pilots training the means of training are also defined. The most important component of the training process is monitoring of cadets’ educational and cognitive activities. The technology of creating cadets-pilots’ integrative theoretical knowledge offered by the author means organization of theoretical training process in special courses based on intersubject communications.